Compliance with Clinical Pathways and Pilot Implementation Impact on Financial Outcome in Hospitals Using National Health Insurance: An Action Research - Rien Rahmi Riandini; Achmad Yudi Arifiyanto; Thinni Nurul Rochmah; Djazuly Chalidyanto; Raissa Manika Purwaningtyas (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Payment for health services with national health insurance applies a prospective method. Hospitals must make efforts so that health services can run efficiently and not cause losses. The problem in this research is the negative difference between the Indonesian Case Based Group (INA-CBG) rates and service costs based on actual patient rates with national health insurance. This study aimed to develop a clinical pathway on 10 top CBG codes with the largest negative differences between INA-CBG and hospital rate. It also evaluated its pilot implementation impact on financial outcomes. Action research was conducted on a sample of the top 10 Case Based Group (CBG) codes with the largest negative difference between INA-CBG rates. One thousand ninety-nine (1099) medical records were analyzed and taken randomly using simple random sampling. Most of the variants found were the provision of consumable medical materials that exceeded standards and the administration of patent medicines outside the national formulary without written medical indications. The value of compliance with the clinical pathway was still below the expected standard (< 80%), especially in medical consumables. Researchers carried out a three-month intervention of a new clinical pathway implementation. The results showed increased compliance with clinical pathways and reduced negative differences between INA-CBG and hospital rates. Clinical pathway audits could reduce the negative difference between INA-CBG and hospital rates.